Anaplastic lymphoma kinase-negative uterine inflammatory myofibroblastic tumor containing the ETV6-NTRK3 fusion gene: a case report. Issue 8 (August 2018) - Takahashi, Akimasa; Kurosawa, Manabu; Uemura, Mao; Kitazawa, Jun; Hayashi, Yoshihiko
Inflammatory myofibroblastic tumors (IMTs) are neoplasms with low malignant potential, and the most common tumor in the lung and orbit. Their occurrence in the uterus is rare. Approximately 50% of IMT patients have anaplastic lymphoma kinase gene ( ALK ) rearrangements. Recent studies described novel fusions involving ROS1, platelet-derived growth factor receptor beta ( PDGFR-β ), and ETS translocation variant ( ETV6 ) genes in a subset of ALK -negative patients. We report a 44-year-old woman with anemia and uterine IMT. Ultrasonography and magnetic resonance imaging revealed a myxoid degenerative myoma-like mass, 7.4 cm in maximum diameter, on the left uterine side wall. Hysterectomy was performed as a definitive treatment. Microscopic examination revealed spindle cell proliferation with numerous lymphocytes and plasma cells. Immunohistochemically, the spindle cells were negative for ALK-1, desmin, and smooth muscle actin. The pathological diagnosis was IMT arising from the uterus. Fluorescence in situ hybridization demonstrated an ETV6– neurotrophic tyrosine kinase, receptor, type 3 gene ( NTRK3 ) translocation but no ALK, ROS1, or PDGFR-β translocations. Lung and abdomen computed tomography at 31 months postoperatively revealed no disease recurrence. This association of an ETV6–NTRK3 fusion oncogene with an ALK -negative uterine IMT increases our understanding of this neoplasm, which may help the development of specific therapies.